2019
DOI: 10.15644/asc53/2/3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Time and Temperature on Salivary Total Antioxidant Capacity, Total Oxidant Status, and Oxidant Stress Index

Abstract: Objective The aim of this study was to compare the effects of short-term storage in two different temperatures on stability of salivary total antioxidant capacity (TAC), total oxidant status (TOS) and oxidant stress index (OSI). Materials and methods Saliva samples were collected from twenty healthy volunteers for the study. An aliquot was selected for immediate analysis and the rest was stored at -20°C and -80°C for a period of 120 days, and analyzes were performed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Bansil et al [14] provide a molecular interpretation on how the structure of mucin leads to entanglements among the biopolymers in solution and create a range of viscosity effects depending upon concentration and mucin type. They suggest that a dilute solution of mucin generally has viscoelastic behavior that depends upon shear rate.…”
Section: Discussionmentioning
confidence: 99%
“…Bansil et al [14] provide a molecular interpretation on how the structure of mucin leads to entanglements among the biopolymers in solution and create a range of viscosity effects depending upon concentration and mucin type. They suggest that a dilute solution of mucin generally has viscoelastic behavior that depends upon shear rate.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to refrain from eating, drinking or brushing their teeth for at least one hour prior to saliva sample collection. All samples were collected in the morning between 7:30 am to 11:30 am to minimize diurinal variations [ 24 , 26 28 ]. In brief, participants were asked to refrain from eating 1-h prior to saliva collection.…”
Section: Methodsmentioning
confidence: 99%
“…U dosadašnjim studijama autori su istaknuli da toplinsko i mehaničko opterećenje značajno utječe na mehanička svojstva materijala alignera te rezultira promjenama u tvrdoći, elastičnosti i čvrstoći (13, 17 -19). Također upozoravaju da te naprave mogu doživjeti promjene u obliku i sastavu u oralnome okruženju zbog čimbenika kao što su temperatura, vlažnost i salivarni enzimi (10,20,21). Razumijevanje mehaničkog ponašanja alignera pod različitim stresom ključno je za optimizaciju njihovih performansi.…”
Section: Uvodunclassified
“…Previous studies have shown that thermal and mechanical loading significantly affect the mechanical properties of aligner materials, thus leading to changes in hardness, elasticity, and strength (13,(17)(18)(19). Also, studies have indicated that aligners may undergo changes in shape and composition in the oral environment due to factors such as temperature, humidity, and salivary enzymes (10,20,21). Understanding the mechanical behavior of aligners under various stresses is essential for optimizing their performance.…”
Section: Priprema Uzorakamentioning
confidence: 99%